A Poem in Two Contexts: Psalm 40:14–18 and Psalm 70 in their Canonical Setting: Festschrift for GTM Prinsloo - Firth, David (Journal for Semitics, 2022)
That Psalms 40:14–18 and 70 are (near) duplicates is well known. Previous research on these psalms has tended to focus on the question of origin, debating which was the original source for the other, with this then used to explain the variances between them, usually with the goal of establishing the original poem. This paper takes a different approach, arguing that the variances between the two are to be explained as evidence of shaping each to its current setting. These variances thus contribute to subtle changes in meaning between them which need to be recognised.
paid
Keywords: Psalms; canonical shaping; text criticism